Investigating the associations between personality functioning, cognitive biases, and (non-)perceptive clinical high-risk symptoms of psychosis in the community - Giulia Rinaldi; Stefan Lerch; Frauke Schultze-Lutter; Stefanie Julia Schmidt; Marialuisa Cavelti; Michael Kaess; Chantal Michel (European Psychiatry)
Abstract